Towards Win-Win : A Labor Reform Strategy to Benefit All - World Bank (World Bank, Washington, DC, 2021)
Indonesia needs more jobs. While 2.1 million jobs have been created on average over the past three years, the 20 percent youth unemployment rate, four times higher than the adult unemployment rate, combined with the growth of the country’s labor force, emphasizes the importance of greater job creation (Sakernas, 2017). Indonesia’s productive age population is now growing. Current changes in the demographic structure will provide Indonesia with a window of opportunity to achieve a demographic bonus during 2020-2030. However, to enjoy optimum benefits, the country’s human resources must able to meet the requirements of the labor market. Therefore, mastery of the skills needed by the labor market, particularly regarding technological and entrepreneurial skills, is critical. (LD FEUI, 2017). It is important to continuously improve both the quantity and quality of jobs created. Employment in Indonesia has been dominated by low productivity sectors, of which 30 percent is employed in the agricultural sector (Sakernas, 2017). Output per agricultural worker is equivalent to only 1/3 of the processing industry sector and 1/2 of the service sector’s output. New job creation has generally taken place in such low productivity sectors, with 65 percent of all new job creation between 2011-2016 taking place in the agricultural, trade and low-end service sectors. The current composition of the labor market has moreover given rise to a division between formal and informal sectors, between skilled and unskilled workers, and between contracted and non-contracted workers. 58 percent of all workers, including employees as well as freelancers, are not covered by employment contracts, meaning that they are more vulnerable to shocks and receive less protection.